Structural Snapshots from the Oxidative Half-reaction of a Copper Amine Oxidase: IMPLICATIONS FOR O(2) ACTIVATION - Johnson, Bryan J. (American Society for Biochemistry and Molecular Biology, 2013)
The mechanism of molecular oxygen activation is the subject of controversy in the copper amine oxidase family. At their active sites, copper amine oxidases contain both a mononuclear copper ion and a protein-derived quinone cofactor. Proposals have been made for the activation of molecular oxygen via both a Cu(II)-aminoquinol catalytic intermediate and a Cu(I)-semiquinone intermediate. Using protein crystallographic freeze-trapping methods under low oxygen conditions combined with single-crystal microspectrophotometry, we have determined structures corresponding to the iminoquinone and semiquinone forms of the enzyme. Methylamine reduction at acidic or neutral pH has revealed protonated and deprotonated forms of the iminoquinone that are accompanied by a bound oxygen species that is likely hydrogen peroxide. However, methylamine reduction at pH 8.5 has revealed a copper-ligated cofactor proposed to be the semiquinone form. A copper-ligated orientation, be it the sole identity of the semiquinone or not, blocks the oxygen-binding site, suggesting that accessibility of Cu(I) may be the basis of partitioning O(2) activation between the aminoquinol and Cu(I).